Cost-Effectiveness of Low-Field Intraoperative Magnetic Resonance in Glioma Surgery - Garcia-Garcia, Sergio; García-Lorenzo, Borja; Ramos, Pedro Roldan; Gonzalez-Sanchez, Jose Juan; Culebras, Diego; Restovic, Gabriela; Alcover, Estanis; Pons, Imma; Torales, Jorge; Reyes, Luis; Sampietro-Colom, Laura; Enseñat, Joaquim (Frontiers in Oncology, 2020)
Object: Low field intraoperative magnetic resonance (LF-iMR) has demonstrated a slight increase in the extent of resection of intra-axial tumors while preserving patient`s neurological outcomes. However, whether this improvement is cost-effective or not is still matter of controversy. In this clinical investigation we sought to evaluate the cost-effectiveness of the implementation of a LF-iMR in glioma surgery. Methods: Patients undergoing LF-iMR guided glioma surgery with gross total resection (GTR) intention were prospectively collected and compared to an historical cohort operated without this technology. Socio-demographic and clinical variables (pre and postoperative KPS; histopathological classification; Extent of resection; postoperative complications; need of re-intervention within the first year and 1-year postoperative survival) were collected and analyzed. Effectiveness variables were assessed in both groups: Postoperative Karnofsky performance status scale (pKPS); overall survival (OS); Progression free survival (PFS) and a variable accounting for the number of patients with a greater than subtotal resection and same or higher postoperative KPS (R-KPS). All preoperative, procedural and postoperative costs linked to the treatment were considered for the cost-effectiveness analysis (diagnostic procedures, prosthesis, operating time, hospitalization, consumables, LF-iMR device, etc). Deterministic and probabilistic simulations were conducted to evaluate the consistency of our analysis. Results: 50 patients were operated with LF-iMR assistance, whilst 146 belonged to the control group. GTR rate, pKPS, R-KPS, PFS and 1-year OS were respectively 13,8%(not significative), 7 points (p<0.05), 17% (p<0.05), 38 days (p<0.05) and 3.7% (not significative) higher in the intervention group. Cost-effectiveness analysis showed a mean incremental cost per patient of 789 € in the intervention group. Incremental cost-effectiveness Ratios were 111 € per additional point of pKPS, 21 € per additional day free of progression and 46 € per additional percentage point of R-KPS. Conclusion: Glioma patients operated under LF-iMR guidance experience a better functional outcome, higher resection rates, less complications, better PFS rates but similar life expectancy compared to conventional techniques. In terms of efficiency, LF-iMR is very close to be a dominant technology in terms of R-KPS, PFS and pKPS.